Tissue Biomarkers in Gastric Cancer Treatment: Present and Future - Giulia Airò; Virginia Agnetti; Fabiana Pratticò; Marianna Peroni; Simona Bui; Giovanni Mura; Maria Urbanowicz-Nijaki; Eleonora Lai; Marco Puzzoni; Fabiana Contu; Nerina Denaro; Mario Scartozzi; et al. (International Journal of Translational Medicine)
The aggressive nature of gastric cancer often leads to late diagnosis and poor prognosis. Chemotherapy and the more recently added immunotherapy remain key treatments for this disease. Several studies have focused on identifying tissue biomarkers with prognostic and/or predictive roles and therefore the therapeutic options are rapidly growing. In this narrative review, we summarize the major tissue biomarkers routinely assessed in clinical practice. In addition, we focus on new evidence about emerging tissue biomarkers that could have a predictive role in future therapeutic approaches and also on the potential role of liquid biopsy in this neoplasm.